2009
DOI: 10.1021/np800792d
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Coxsackie Virus B3 Norsesquiterpenoids from the Roots of Phyllanthus emblica

Abstract: Three new norsesquiterpenoid glycosides, 4'-hydroxyphyllaemblicin B (1) and phyllaemblicins E (2) and F (3), were isolated from the roots of Phyllanthus emblica, together with three known compounds, phyllaemblic acid (4), phyllaemblicin B (5), and phyllaemblicin C (6). Of these, 3 is a new norsesquiterpenoid dimer. The structures of 1-3 were established by spectroscopic data information and by acidic hydrolysis. The isolated compounds, together with two other known analogues, phyllaemblic acid methyl ester (7)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…Interestingly, T. bellerica, another component of this formula has recently been shown to possess antispasmodic effect with similar mode of action (Gilani et al, 2008a). The plant has also been shown to possess antibacterial activity (Saeed and Tariq, 2007), while some of its norsesquiterpenoid glycosides are reported to have antiviral effects (Liu et al, 2009). Such activities of the plant could account additional benefit providing a wider cover for its use in diarrhea of different etiologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, T. bellerica, another component of this formula has recently been shown to possess antispasmodic effect with similar mode of action (Gilani et al, 2008a). The plant has also been shown to possess antibacterial activity (Saeed and Tariq, 2007), while some of its norsesquiterpenoid glycosides are reported to have antiviral effects (Liu et al, 2009). Such activities of the plant could account additional benefit providing a wider cover for its use in diarrhea of different etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…Its roots are reported to contain norsesquiterpenoid glycosides, such as, phyllaemblicins A-C, E and F, and phyllaemblic acid, a methyl ester (Liu et al, 2009). The leaves, bark and fruits of Phyllanthus emblica are found rich in phenolic contents (Bajpai et al, 2005;Chalise et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, PEL is traditionally used to control hepatitis, regulation of stomach movements, cancer, and act as immunomodulator [18]. Likewise, non sesquiterpenoids obtained from PEL has shown antiviral activity against Coxsachie virus B 3 [19]. GGL has traditionally been used as anti-inflammatory agent, antibacterial agent, expectorant, mild laxative and diuretic [20].…”
Section: Introductionmentioning
confidence: 99%
“…Phyllanthus emblica, a euphorbiaceous plant is widely distributed in subtropical and tropical areas of India. It is used as antimicrobial (Rani and Khullar 2004) and the phenolic compounds including the major components 5-8 from the fruit juice, 8, 9, and 12 from the branches and leaves, and proanthocyanidin polymers from the roots of P. emblica showed stronger inhibition against B16F10 cell growth than against HeLa and MK-1 cell growth (Zhang et al 2004).Three new norsesquiterpenoid glycosides, 4′-hydroxyphyllaemblicin B (1) and phyllaemblicins E (2) and F (3), were isolated from the roots of P. emblica, together with three known compounds, phyllaemblic acid (4), phyllaemblicin B (5), and phyllaemblicin C (6) evaluated for their antiviral activity toward coxsackie virus B3 (CVB3) by an in vitro cytopathic effect inhibitory assay (Liu et al 2009). Dapper et al (2007) reported that the aqueous extract of the leaves and stem of Phyllantus amarus displayed antiplasmodial effects against P. berghei infection using Swiss albino mice as models.…”
Section: Introductionmentioning
confidence: 99%